My memories on Robert L. Dressler (1927 - 2019): Extraordinary botanist and human being - Morales, Carlos O. (Revista de Biología Tropical, 2020)
Abstract: This text honors the memory of the great orchidologist Robert L. Dressler, who was considered as the best world orchid specialist along decades. It includes biographical data, jottings and facts about Dr. Dressler’s work, specially in Costa Rica. He described 12 superior Orchidaceous taxa, 18 orchid genera, 230 orchid species, 10 species of other plant groups, and 38 bee species. Moreover, he published 162 new name combinations of Orchidaceae and 10 combinations of Euphorbiaceae, nine books, and 252 scientific papers. The scientific work of Dr. Dressler has had great positive impact on botanists, students, and orchid aficionados.